Laser driven 2D heterostructure nanocomposite membranes with bimodal photothermal and photodynamic functions - Congcong Wang; Yu Meng; Cuilu Xi; Yinyan Li; Jianbin Zhang; Junqiang Dong; Yanbang Lian; Shiqing Xu; Gongxun Bai; Xin Sun (Journal of Materiomics)
To ablate tumor tissues safely and efficiently occupy a high priority in physical cancer therapy. However, it is still a challenge to realize high conversion efficiency of photothermal reagents and multi-functions with low health risks. Herein, nano-heterostructure membrane was synthesized by composting MoSe2:Nd nanosheets and graphene nanoflakes for improving the therapy efficiency and efficacy. It not only exerts fulfilling photothermal behaviors under 808 nm laser excitation, but also exhibits outstanding laser-induced photodynamic performance due to photogenerated carriers transfer from unique physical heterostructure. With bimodal photothermal/photodynamic therapy potential, the heterojunction structure is incorporated into the polydimethylsiloxane (PDMS) film and subcutaneously implanted into animate bodies, which further facilitate biomedical safety and experiment operability in tumor treatments, cutting off the possible risks arising from direct injection. In vitro photothermal properties and biomedical experiments strongly proof the composite film can exert intense photothermal response at laser excitation and possess considerably satisfactory biocompatibility, effectively eliminating tumor tissues without undesirable damage and pathological changes to normal organs.